Thrombin spatial distribution determines protein C activation during hemostasis and thrombosis - Marar, Tanya T; Matzko, Chelsea N; Wu, Jie; Esmon, Charles T; Sinno, Talid; Brass, Lawrence F; Stalker, Timothy J; Tomaiuolo, Maurizio (Blood, 2022)
Rebalancing the hemostatic system by targeting endogenous anticoagulant pathways, like the protein C (PC) system, is being tested as a means of improving hemostasis in patients with hemophilia. Recent intravital studies of hemostasis demonstrated that, in some vascular contexts, thrombin activity is sequestered in the extravascular compartment. These findings raise important questions about the context-dependent contribution of activated PC (APC) to the hemostatic response, because PC activation occurs on the surface of endothelial cells. We used a combination of pharmacologic, genetic, imaging, and computational approaches to examine the relationships among thrombin spatial distribution, PC activation, and APC anticoagulant function. We found that inhibition of APC activity, in mice either harboring the factor V Leiden mutation or infused with an APC-blocking antibody, significantly enhanced fibrin formation and platelet activation in a microvascular injury model, consistent with the role of APC as an anticoagulant. In contrast, inhibition of APC activity had no effect on hemostasis after penetrating injury of the mouse jugular vein. Computational studies showed that differences in blood velocity, injury size, and vessel geometry determine the localization of thrombin generation and, consequently, the extent of PC activation. Computational predictions were tested in vivo and showed that when thrombin generation occurred intravascularly, without penetration of the vessel wall, inhibition of APC significantly increased fibrin formation in the jugular vein. Together, these studies show the importance of thrombin spatial distribution in determining PC activation during hemostasis and thrombosis.